Martin Luther on the Legitimacy of Resisting the Emperor - Raley, J. Michael (Journal of law and religion, 2022)
Martin Luther (1483-1546) repeatedly addressed the question of whether political resistance might be directed lawfully against sovereign rulers if they acted tyrannically in light of the Apostle Paul's admonition in Romans 13 to honor divinely ordained secular authority. The situation became acute during the 1530s, when the forces of Emperor Charles V and the German Catholic princes threatened to reimpose Catholicism in the Lutheran territories by force. Amidst the crisis, Luther accepted legal arguments delegitimizing Charles as emperor, and, in 1539, with both sides mobilized for war, he contributed the theological argument that the emperor was the mercenary of a papal Antichrist and Beerwolff. Despite viewing the struggle in such apocalyptic terms, however, Luther's own words from the 1520s until his death reveal that his insistence upon obeying "legitimate" authority never varied. Only if commanded to violate godly law were Christian subjects to disobey their rulers and suffer the consequences. After Luther's death, Lutheran resistance theory continued to evolve and interact with Calvinist theory. Thus it exerted a long-term impact both within and well beyond the church when it was appropriated by the Magdeburg pastors, French Huguenots, Dutch revolutionaries, and English Puritans, though not always as Luther would have intended.